Forever prisoners: how the United States made the world's largest immigration detention system - Young, Elliott (Oxford University Press, 2021)
"The United States locks up more than half a million non-citizens every year for immigration-related offenses; on any given day, more than 50,000 immigrants are held in detention in hundreds of ICE detention facilities spread across the country. This book provides an explanation of how, where, and why non-citizens were put behind bars in the United States from the late nineteenth century to the present. Through select granular experiences of detention over the course of more than 140 years, this book explains how America built the world's largest system for imprisoning immigrants. From the late nineteenth century, when the US government held hundreds of Chinese in federal prisons pending deportation, to the early twentieth century, when it caged hundreds of thousands of immigrants in insane asylums, to World War I and II, when the Federal Bureau of Investigation (FBI) declared tens of thousands of foreigners "enemy aliens" and locked them up in Immigration and Naturalization Service (INS) camps in Texas and New Mexico, and through the 1980s detention of over 125,000 Cuban and almost 23,000 Haitian refugees, the incarceration of foreigners nationally has ebbed and flowed. In the last three decades, tough-on-crime laws intersected with harsh immigration policies to make millions of immigrants vulnerable to deportation based on criminal acts, even minor ones, that had been committed years or decades earlier. Although far more immigrants are being held in prison today than at any other time in US history, earlier moments of immigrant incarceration echo present-day patterns"--